2001
DOI: 10.1029/2001ja900109
|View full text |Cite
|
Sign up to set email alerts
|

ROCSAT 1 ionospheric plasma and electrodynamics instrument observations of equatorial spread F: An early transitional scale result

Abstract: Abstract. Ion density and vertical ion drift velocity sampled at 1024 Hz from the ROCSAT 1 satellite are used to examine the behavior of horizontal structures in equatorial spread F near 600 km altitude. An initial investigation shows that at scale sizes less than 100 m the relationships between the vertical drift and density structure are distinguished by the bulk plasma flow in the structure and by the background gradient in the density. Two adjacent equatorial bubble structures are examined: one in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 20 publications
4
39
0
Order By: Relevance
“…Its orbital altitude is 600 km, and the inclination angle is about 35 • (e.g. Su et al, 2001). Note that the orbit altitude is higher than that of CHAMP.…”
Section: Instrumentation and Methodsmentioning
confidence: 99%
“…Its orbital altitude is 600 km, and the inclination angle is about 35 • (e.g. Su et al, 2001). Note that the orbit altitude is higher than that of CHAMP.…”
Section: Instrumentation and Methodsmentioning
confidence: 99%
“…High-resolution observations with the EAR, never before realized, must play an important role in various studies of the equatorial atmosphere and ionosphere. It is expected that the EAR will be operated in collaboration with other existing networks of radars, such as those mentioned in the Introduction, satellites such as TIMED (Thermosphere Ionosphere Mesosphere Energetics and Dynamics) of the USA and ROCSAT-1 of the Republic of China (Taiwan) [Su et al, 2001], and other ground-based radio and optical sensors. The EAR is expected to proceed to study the hierarchical structure of atmospheric variations in the equatorial region using the data from these instruments in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The ESF studies using ionosonde data (Sales et al, 1996;Stephan et al, 2002;Whalen, 2002), the Global Positioning System (GPS) (Aarons et al, 1996;Mendillo et al, 2000Mendillo et al, , 2001, radars (Woodman and LaHoz, 1976;Hysell and Burcham, 1998), satellite (Huang et al, 2001;Su et al, 2001), and numerical modeling (Maruyama, 1988;Sultan, 1996) have demonstrated the general morphology of the ESF phenomenon. Now, it is known that there are some candidate mechanisms helping the ESF development.…”
Section: Introductionmentioning
confidence: 99%